Highly tumorigenic hepatocellular carcinoma cell line with cancer stem cell-like properties. - Benoit Lacoste; Valérie-Ann Raymond; Shamir Cassim; Pascal Lapierre; Marc Bilodeau (PLoS ONE)
There are limited numbers of models to study hepatocellular carcinoma (HCC) in vivo in immunocompetent hosts. In an effort to develop a cell line with improved tumorigenicity, we derived a new cell line from Hepa1-6 cells through an in vivo passage in C57BL/6 mice. The resulting Dt81Hepa1-6 cell line showed enhanced tumorigenicity compared to Hepa1-6 with more frequent (28±12 vs. 0±0 lesions at 21 days) and more rapid tumor development (21 (100%) vs. 70 days (10%)) in C57BL/6 mice. The minimal Dt81Hepa1-6 cell number required to obtain visible tumors was 100,000 cells. The Dt81Hepa1-6 cell line showed high hepatotropism with subcutaneous injection leading to liver tumors without development of tumors in lungs or spleen. In vitro, Dt81Hepa1-6 cells showed increased anchorage-independent growth (34.7±6.8 vs. 12.3±3.3 colonies; P<0.05) and increased EpCAM (8.7±1.1 folds; P<0.01) and β-catenin (5.4±1.0 folds; P<0.01) expression. A significant proportion of Dt81Hepa1-6 cells expressed EpCAM compared to Hepa1-6 (34.8±1.1% vs 0.9±0.13%; P<0.001). Enriched EpCAM+ Dt81Hepa1-6 cells led to higher tumor load than EpCAM- Dt81Hepa1-6 cells (1093±74 vs 473±100 tumors; P<0.01). The in vivo selected Dt81Hepa1-6 cell line shows high liver specificity and increased tumorigenicity compared to Hepa1-6 cells. These properties are associated with increased expression of EpCAM and β-catenin confirming that EpCAM+ HCC cells comprise a subset with characteristics of tumor-initiating cells with stem/progenitor cell features. The Dt81Hepa1-6 cell line with its cancer stem cell-like properties will be a useful tool for the study of hepatocellular carcinoma in vivo.